Antioxidant activity, inhibition of angiotensin I converting enzyme (ACE) and antibacterial activity of buffalo caseinate protein hydrolysates and their fractions (Research, Society and Development, 2020)
In the present study, buffalo milk caseinate hydrolysates produced by bromelain, neutrase, papain and trypsin were ultra-filtered and different fractions were assessed for antioxidant, inhibition of angiotensin converting enzyme and antimicrobial activity. Biological potential was assessed by a number of metrics: ability to remove radicals of 2,2'-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid), 2,2'-diphenyl-1-picrylhydrazyl (DPPH) and hydroxyls; copper and iron chelation; antidiabetic properties; antihypertensive assay; and antibacterial activity against Escherichia coli ATCC 25922, Listeria monocytogenes ATCC 19114, Salmonella typhimurium ATCC 14028 and Staphylococcus aureus ATCC 25923 strains. The tests for scavenging of hydroxyl radicals and DPPH revealed a greater potential in the 3–10 kDa fractions. Iron chelation activity >70% was observed in all the fractions, including 60% in fractions >10 kDa. α-Amylase inhibition and antihypertensive activity was optimal in the